Of Both Sides, Rethinking Nigeria Tertiary Education: The “Real Deal” Radio Drama Experience: Array - Azunwo, Eziwho Emenike (Acta Universitatis Danubius. Relationes Internationales, 2022)
In contemporary times such as ours, education has become characteristically consummate to the service of humanity and in the provision of cutting edge technologies that have helped in building formidable and egalitarian culture. Education has become of symbol of civilisation and socialisation whether in mores or otherwise. It enables man to harness nature and utilise the resources for well-being and improvement of his existence. In no less argument, it has become the very key needed for the betterment of up-to-the-minute living society. Beyond the credibility of the foreground, it is yet a painful reality to earnestly bring to the fore that Nigerian university education has remained in the lowest shambles, notwithstanding the legitimate struggles of Academic Staff Union of Universities (ASUU). The failing state of university education in the country has seen many Nigerians patronize foreign and private universities. The fact remains that universities in Nigeria have long been institutions left for the low and helpless to scramble upon, in the name of education. Whereas, ASUU has made frenetic progress at improving education, the hefty criticisms punched at the union by many Nigerians aptly out of ignorance and in most cases cant, the union has been profoundly limited in her progressive flow hence, this study. The study aims at correcting the misconceptions carried against the union by informing largely through the mass media (Radio drama). George Gerbner’s “General Model” theory of communication supplements this discourse. This research studies a radio drama entitled “Real Deal”. The radio drama’s script underwent a critical analysis as the research discovers that ASUU has been the only committed body so far in Nigeria fighting for the revival of education, while the Federal Government of Nigeria (FGN) regularly opposes ASUU’s positions. To this end, the study recommends that not only should ASUU be supported by all and sundry but their agitations should equally be looked upon because a deliberate attendance to them means the revival of Nigeria educational sector.